Estimation and comparison of dental, skeletal and chronologic age in Bangalore south school going children - P H Shilpa; R S Sunil; K Sapna; N C Kumar (Wolters Kluwer Medknow Publications, 2013)
Objective : Precise evaluation of the developmental stages of a child is an integral part of both diagnosis and treatment planning of pediatric patients and also essential in forensic medicine and dentistry. As human growth shows considerable variation in chronological age, physiological maturity is preferred over chronological age in the estimation of person's exact age. Materials and Methods : Two hundred and fifty children consisting of 124 girls and 126 boys were selected randomly from the age group of 6-15 years. They were divided into 10 groups based on their age. The chronological age was determined by their date of birth as per the school records. An orthopantomogram and left hand-wrist radiographs was taken for each child to assess the dental age through Demirjian's method and skeletal age through the atlas of Greulich and Pyle's method respectively. Result : The dental age showed a significant correlation (P < 0.05) with chronological age in group 1 and 5 in males and group 3 and 7 females, whereas skeletal age showed a significant correlation with chronological age in group 3, 5, 9, and 10 in males and 1, 2, 5, 9, and 10 years in females. Conclusion : Demirjian's method of dental age estimation and Greulich and Pyle's method of skeletal age estimation showed accuracy only in certain age groups in the school children of Bangalore.